2019
DOI: 10.5937/fmet1903518j
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thermo-electrical property of materials on Powder Mixed Electrical Discharge Machining

Abstract: Powder Mixed Electrical Discharge Machining (PMEDM) is considered as one of the viable methods to machine the materials which are hard and tough but with appreciable thermo-electrical properties. In PMEDM, it has been established that machinability is enhanced by adding additives in the form of fine powders in the spark gap of EDM process. In this investigation, the role of the thermo-electrical properties of workpiece on PMEDM process has been studied. Materials with distinct thermoelectric property, namely M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…OC tends to rise on increasing M F from 0.15 to 0.45 T as illustrated in Supplementary Fig. 7 20 comprises of both negative and positive ions which under the influence of Lorentz force changes path of ions and causing more collusions between the ions. Due to this temperature in plasma channel increases which expand the channel causing enlargement in OC.…”
Section: Effect Of Process Parametersmentioning
confidence: 97%
See 1 more Smart Citation
“…OC tends to rise on increasing M F from 0.15 to 0.45 T as illustrated in Supplementary Fig. 7 20 comprises of both negative and positive ions which under the influence of Lorentz force changes path of ions and causing more collusions between the ions. Due to this temperature in plasma channel increases which expand the channel causing enlargement in OC.…”
Section: Effect Of Process Parametersmentioning
confidence: 97%
“…Results obtained revealed power concentration have significant effect at higher current. Jeavudeen et al 20 during EDM of mild steel and aluminium with addition of fine alumina powder in dielectric witnessed increase in MRR and tool wear index. Patel and Pradhan 21 analysed the influence of process parameters on surface roughness during EDM of Al 6061 alloy SiC powder mixed in dielectric.…”
Section: Introductionmentioning
confidence: 99%
“…Based on Hadi et al [22], it was reported that experiments were conducted with 3 different tools, namely copper, graphite, and copper-graphite, on MONEL 400, and it was found that the copper-graphite tool gave optimal results in terms of MRR and Ra. Jeavudeen et al [23] investigated the effect of three process parameters (gap duty, duty cycle, and flow rate of PM) with aluminum and mild steel (workpiece) by using copper (12 mm dia) as an electrode. They observed that the parameters increase showed the MRR rise (17.52%) in Aluminum and TWI low (4.08%) in mild steel using L9 OA design.…”
Section: Introductionmentioning
confidence: 99%
“…Various researchers have observed that the performance of PMEDM in terms of machinability has been enhanced by the addition of additive powders with distinct thermo-electrical properties, and at different particle sizes, concentrations, densities etc., [14][15][16]. Also the thermo-electrical property of the workpiece materials do affects the machinability of the materials [17].…”
Section: Introductionmentioning
confidence: 99%